Does brand community participation lead to early new product adoption? The roles of networking behavior and prior purchase experience - Jiang, Ying; Liao, Junyun; Pang, Jiecong; Hu, Hsin-Li (Frontiers in Psychology, 2023)
Consumers’ adoption behavior is critical to the success of new products, but the effects of brand communities on new product adoption have rarely been investigated. In this study, we draw on network theory to examine how consumer participation in brand communities (in terms of participation intensity and social networking behaviors) affects the adoption of new products. We collected longitudinal data from 8,296 members of an online community of a well-known smartphone brand to assess the factors influencing new product adoption. The results from applying a hazard model indicated that brand community participation increases the speed of adoption of new products. The positive effect of members’ out-degree centrality on new product adoption was found to be significant, but in-degree centrality only had an effect when users had previous purchasing experience. These findings extend the literature by revealing how new products are disseminated across brand communities. The study also makes theoretical and practical contributions to the literature on brand community management and product marketing.